Istibdal Wakaf Harta Bergerak Dan Tidak Bergerak Menurut Undang-Undang Wakaf Dan Mazhab Syafi’i - Ipan Yusup; Suaib Lubis (Peduli Riset dan Pengabdian Masyarakat, 2023)
Istibdal waqf is replacing the waqf property with another because there is a benefit or must be replaced on condition that the muwakif determines that it is permissible to make istibdal of the waqf assets. Basically the sale of waqf assets is prohibited, because the purpose of waqf is so that these assets can be used forever. Istibdal of waqf assets in Indonesia has occurred several times. In some cases of selling waqf assets, the type of waqf assets being sold is land. From this background, it is necessary to conduct research by referring to laws and fiqh schools that are adhered to by the majority of the Indonesian population. This study aims to determine the istibdal of waqf of movable and immovable objects according to waqf laws, the Madhhab Shafi'i of thought, and to choose a strong opinion between the two. The type of research used by the authors is library research with a qualitative approach. The datas were collected using documentation techniques, with primary data from fiqh books of the Shafi'i and Law Number 41 of 2004 concerning Waqf, and secondary data from books, journals, and expert opinions. The datas are then collected, collated, and analyzed. The results of his research are: first, istibdal waqf according to the Waqf Law is basically prohibited, except in conditions as described in Article 41 of the Waqf Law; second, the Madhhab Shafi'i forbids istibdal; third, the researcher chose to strengthen the istibdal provisions regulated in the Waqf Law.